1983
DOI: 10.1002/ajh.2830150108
|View full text |Cite
|
Sign up to set email alerts
|

Sustained post‐transfusion granulocyte count increments following transfusion of leukocytes obtained from donors with chronic myelogenous leukemia

Abstract: Leukocyte transfusions from patients with chronic myelogenous leukemia (CML) and elevated WBC counts were given to 14 patients with acute leukemia for the treatment of 16 infectious episodes. The WBCs were not irradiated to determine if engraftment with production of granulocytes would occur following infusion of immature myeloid elements. No recipient was alloimmunized by clinical and serologic criteria. High leukocyte yields were obtained using a variety of differential centrifugation techniques with a mean … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

1985
1985
2014
2014

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 36 publications
(13 citation statements)
references
References 33 publications
0
13
0
Order By: Relevance
“…Because immature myeloid progenitors were obtained from CML donors, sustained levels of circulating granulocytes were commonly seen for a number of days after single transfusions owing to continued differentiation of the myeloid precursors. Interestingly, it was also shown that the leukocyte alkaline phosphatase levels were markedly increased in the granulocytes tested ex vivo after circulation in the infected host, whereas they were characteristically decreased in the CML donors [6].…”
Section: A Brief History Of the Use Of Granulocyte Transfusionmentioning
confidence: 97%
See 1 more Smart Citation
“…Because immature myeloid progenitors were obtained from CML donors, sustained levels of circulating granulocytes were commonly seen for a number of days after single transfusions owing to continued differentiation of the myeloid precursors. Interestingly, it was also shown that the leukocyte alkaline phosphatase levels were markedly increased in the granulocytes tested ex vivo after circulation in the infected host, whereas they were characteristically decreased in the CML donors [6].…”
Section: A Brief History Of the Use Of Granulocyte Transfusionmentioning
confidence: 97%
“…Because immature myeloid progenitors were obtained from CML donors, sustained levels of circulating granulocytes were commonly seen for a number of days after single transfusions owing to continued differentiation of the myeloid precursors. Interestingly, it was also shown that the leukocyte alkaline phosphatase levels were markedly increased in the granulocytes tested ex vivo after circulation in the infected host, whereas they were characteristically decreased in the CML donors [6].Although the CML transfusions were well tolerated and demonstrably of benefit, there was increasing reluctance to utilize donors with 'cancer', with a shift towards the collection of cells from normal donors. In parallel, in the early 1970s, both continuous flow (CFC) and intermittent flow centrifugation (IFC) apheresis devices were developed which utilized rouMed Mycol Downloaded from informahealthcare.com by Nanyang Technological University on 08/24/15…”
mentioning
confidence: 96%
“…Homografts have been described in recip ients of leukocyte transfusion obtained from CML patients [15,16]. However, all of our leukocyte concentrates were irradiated with 15 Gy, which is in general considered suffi cient to prevent cell division and engraftment of a homo graft.…”
Section: Casementioning
confidence: 99%
“…negligible (b0.5%) in several other large studies [44][45][46]. The fact that CML cells could engraft transiently, eradicate or prevent infection during the neutropenic period, and subsequently be rejected upon endogenous immune recovery of the host illustrates principles that underlie NEACT.…”
Section: Historical Perspectivementioning
confidence: 97%
“…In the 1960s-1980s, non-irradiated neutrophils from chronic myeloid leukemia (CML) patients were transfused to unrelated, nonalloimmunized AML patients receiving induction or re-induction chemotherapy as a means of providing transient engraftment for supportive care [42][43][44][45][46]. This strategy antedated the use of therapeutic granulocyte transfusions obtained from normal donors (because yields were higher from CML patients [47]) and antedated granulocytecolony stimulating factor (G-CSF) therapy.…”
Section: Historical Perspectivementioning
confidence: 99%